1997
DOI: 10.1159/000213840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the APP Gene Family in Brain Cells, Brain Development and Aging

Abstract: The Alzheimer’s βA4-amyloid protein precursor (APP) and the APP-like proteins (APLPs) are transmembrane glycopro-teins with a similar modular domain structure. Alternatively spliced exons found in both genes comprise a Kunitz protease inhibitor domain encoding exon, and another exon within the divergent regions adjacent to the transmembrane domain, i.e. exon 15 of the APP gene and an exon encoding 12 residues in APLP2. Omission of the latter exons in L-APP and L-APLP2 isoforms, respectively, generates a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…By this means, APP could be coimmunoprecipitated from WT and APLP2−/−, but not from APP−/− and APLP1−/− brain samples (Figure 6A), showing specific heterointeraction of APP and APLP1 in vivo . In mouse brain, at least three distinct forms of APP with molecular weights of 100, 108, and 120 kDa were detected (Figure 6A; as indicated), likely representing different post‐translationally modified APP695 species (Sandbrink et al , 1997). Interestingly, only the mature, high‐molecular‐weight forms of APP with molecular weights of 108 and 120 kDa were coimmunoprecipitated with APLP1 (Figure 6A), suggesting that a particular pool of APP exists in complex with APLP1 in vivo .…”
Section: Resultsmentioning
confidence: 91%
“…By this means, APP could be coimmunoprecipitated from WT and APLP2−/−, but not from APP−/− and APLP1−/− brain samples (Figure 6A), showing specific heterointeraction of APP and APLP1 in vivo . In mouse brain, at least three distinct forms of APP with molecular weights of 100, 108, and 120 kDa were detected (Figure 6A; as indicated), likely representing different post‐translationally modified APP695 species (Sandbrink et al , 1997). Interestingly, only the mature, high‐molecular‐weight forms of APP with molecular weights of 108 and 120 kDa were coimmunoprecipitated with APLP1 (Figure 6A), suggesting that a particular pool of APP exists in complex with APLP1 in vivo .…”
Section: Resultsmentioning
confidence: 91%
“…APP is ubiquitously expressed in mammalian cells with a broad tissue distribution. The APP splice variant containing 695 amino acids is expressed at higher levels in neurons, whereas the 751‐ and the 770‐residues isoforms are widely expressed in non‐neuronal cells but also occur in neurons 5–7 . All three isoforms are potentially amyloidogenic, since they share the same Abeta, transmembrane, and intracellular domains.…”
Section: Introductionmentioning
confidence: 99%
“…22 No APLP1 spliced transcripts have been discovered so far. Detailed alternative splicing patterns of APP and APLP2 have been previously described and reviewed by Sandbrink et al 23 APLP2 is widely expressed in neural and non-neural tissues. 6,24,25 In situ hybridization and quantitative polymerase chain reaction revealed that APLP2 and APP mRNA are expressed in similar, if not identical, neuronal populations and at similar levels.…”
mentioning
confidence: 99%